Co-designing solutions to enhance access and engagement in pediatric telerehabilitation - Reitzel, Meaghan; Letts, Lori; Lennon, Cynthia; Lasenby-Lessard, Jennifer; Novak-Pavlic, Monika; Di Rezze, Briano; Phoenix, Michelle (Frontiers in Rehabilitation Sciences, 2023)
Introduction: Prior to the COVID-19 pandemic, children's therapy appointments provided by Ontario's publicly-funded Children's Treatment Centre (CTCs) primarily occurred in-person. With COVID-19 restrictions, CTCs offered services via telerehabilitation (e.g., video, phone), which remains a part of service delivery. CTC data shows that families experience barriers in attending telerehabilitation appointments and may need supports in place to ensure service accessibility. Our study aimed to co-design innovative solutions to enhance access and engagement in ambulatory pediatric telerehabilitation services. This manuscript reports the co-design process and findings related to solution development. Methods: This research project used an experience based co-design (EBCD) approach, where caregivers, clinicians and CTC management worked together to improve experience with telerehabilitation services. Interview data were collected from 27 caregivers and 27 clinicians to gain an in-depth understanding of their barriers and successes with telerehabilitation. Using qualitative content analysis, data from the interviews and co-design meetings were analyzed and findings related to the solutions developed are presented. Findings: Four topics were identified from the interview data that were selected as focii for the co-design meetings. Findings from the codesign meetings emphasized the importance of communication, consistency and connection (the 3C's) in experiences with telerehabilitation. The 3C's are represented in the co-designed solutions aimed at changing organizational processes and generating tools and resources for telerehabilitation services. Discussion: The 3C's influence experiences with telerehabilitation services. By enhancing 2 This is a provisional file, not the final typeset article the experience with telerehabilitation, families will encounter fewer barriers to accessing and engaging in this service delivery model.